Should a casino be legalized in Singapore? - Chew, Andy Kai Yeow. (2008)
The purpose of this paper is to examine the possible economic and social impacts that Singapore is likely to experience in the event of casino gaming legalization. Consequently, this paper draws a conclusion on whether a casino should be legalized in Singapore and offers some suggestions on areas of future research.